2017
DOI: 10.1007/s40626-017-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

Root traits and their potential links to plant ideotypes to improve drought resistance in common bean

Abstract: Drought stress limits growth and yield of crops, particularly under smallholder production systems with minimal use of inputs and edaphic limitations such as nitrogen (N) deficiency. The development of genotypes adapted to these conditions through genetic improvement is an important strategy to address this limitation. The identification of morpho-physiological traits associated with drought resistance contributes to increasing the efficiency of breeding programs. A set of 36 bean genotypes belonging to the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 42 publications
4
40
0
3
Order By: Relevance
“…When yield was compared with grain Δ 13 C, only SEA 5 and BAT 477 were consistently classified as water spenders, and SER 16 as a water saver. The classification of SEA 5 and BAT 477 as water spenders is consistent with previous studies that identified them as deep rooting genotypes that can access water deeper in the soil profile (White et al, 1990; Rao, 2014; Polania et al, 2017b). On the other hand, the water saver genotype, SER 16, likely was able to produce high yields under water‐limited conditions due to its capacity to remobilize previously fixed photosynthates to seed (Polania et al, 2016b).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…When yield was compared with grain Δ 13 C, only SEA 5 and BAT 477 were consistently classified as water spenders, and SER 16 as a water saver. The classification of SEA 5 and BAT 477 as water spenders is consistent with previous studies that identified them as deep rooting genotypes that can access water deeper in the soil profile (White et al, 1990; Rao, 2014; Polania et al, 2017b). On the other hand, the water saver genotype, SER 16, likely was able to produce high yields under water‐limited conditions due to its capacity to remobilize previously fixed photosynthates to seed (Polania et al, 2016b).…”
Section: Discussionsupporting
confidence: 89%
“…This was in stark contrast with other genotypes such as BAT 881, CAL 143, and DOR 364, which had LAIs in the TDS environment that were only ?39% of those in the WW environment. Similar to BAT 477, G21212 and SEA 5 were among the genotypes with high LAI under TDS, which was probably related to greater soil exploration for water and nutrients associated with deeper roots, as previously reported for these genotypes (White et al, 1990;Polanía et al, 2009;Beebe et al, 2013;Polania et al, 2017b;Rao et al, 2017). However, since rooting depth was not measured in the present study, it is possible that mechanisms other than rooting depth (e.g., greater C remobilization) also played a role.…”
Section: Impact Of Water Availability On Yield and Physiological Andsupporting
confidence: 87%
See 3 more Smart Citations